The Role of Parents on the Care of Tolls during the Covid-19 Pandemic - Dewi Modjo; Andi Akifa Sudirman; Riskawaty Nuna; Mutya Datungsolang; Suparjo A. Nasibu (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
Toddlers are one of the age groups that are vulnerable to being infected with Covid-19, a disease caused by the SARS-Cov 2 Virus which has become a global pandemic since March 2020. The age limit for toddlers is 1-3 years (toddlers) and 3-5 years (pre-school). Therefore, the care of toddlers during the COVID-19 pandemic must be adjusted to the health protocols set by the government to break the chain of transmission. This is the goal of community service activities, namely to increase parents' knowledge by conducting counseling on how